Influence of riboflavin and ultraviolet-light treatment on plasma proteins – protein S and alpha 2-antiplasmin – in relation to the time of administration - Gojkov Dragana; Balint Bela; Dejanović Bratislav; Vučetić Dušan (Vojnosanitetski Pregled)
Background/Aim. After the introduction of a careful selection procedure for blood donors and the implementation of highly sensitive screening tests for transfusion-transmitted infections (TTIs), blood has become a very safe product concerning TTIs. However, due to the existence of a “window” period during which these “markers” cannot be detected, as well as the emergence of new pathogens, the risk is still present. Implementation of pathogen reduction technology (PRT) provides a proactive approach to improving blood safety. By damaging nucleic acids, PRT selectively inactivates pathogens and leucocytes. Nevertheless, during the process, plasma proteins are also damaged to some extent. The aim of this study was to conclude whether there is a difference in the effect of PRT on protein S (PS) and alpha 2-antiplasmin (α2AP) regarding the time of inactivation: inactivation immediately after plasma separation from whole blood (before freezing) vs. inactivation after freezing/thawing. Methods. The voluntary donors’ blood is taken into a quadruple bag system, centrifuged, and separated into blood products. Control group plasma was first inactivated by the Mirasol® PRT system and then frozen. Experimental group plasma was immediately frozen and, after four months, thawed and inactivated. PS and α2AP activity was examined in samples after separation, inactivation, and thawing. Results. Analyzing PS and α2AP activity, no statistically significant difference was found between the initial samples. The trend of protein activity reduction after inactivation and freezing/thawing was present in both groups but without a statistically significant intergroup difference. Conclusion. No statistically significant difference was found between the activity values of PS and α2AP after immediate inactivation, before freezing, and after freezing/thawing, making stored plasma units suitable for safe and efficient inactivation directly before clinical use and according to the patient’s blood type.